Water quality study on UNIMAS lake - Muhammad Shaiful, Nordin (Universiti Malaysia Sarawak (UNIMAS), 2009)
Environmental engineering studies include a special area of study, which focuses about water and wastewater treatment and water quality control. Another important thing related to environmental engineering is the study about the Water Quality Index (WQI). WQI is the best approach for simulating the physical, chemicals, and biological changes in the aquatic systems. The aim of this study is to determine the WQI for UNIMAS lake and to classify the water based on the Department of Environmental standards and the Interim National Water Quality standards for Malaysia. This study focuses on the physical and chemical parameters such as Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3- N), Total Suspended Solids (TSS) and Hydrogen Ion Concentration (pH). Six experimental works involved in physical and chemical parameter was carried out to finalize all the parameter value before determining the WQI for UNIMAS lake. From this study, the value of WQI for UNIMAS lake is 91.44 and the lake can be classified as “Clean”. The lake also can be classified as “Class II” which is suitable for water supply with a conventional treatment required, suitable for sensitive aquatic species and also suitable for recreational use with body contact.